Ibn Abi El-Isboa El-Masseri’s Contribution to Critical and Rhetoric Terminology in his books: ‘Tahrir El-Tahbir’and ‘Badia El-Quran’. - Saioud, Fawzia (Journal of Human Sciences, 2021)
The critical and rhetorical terms constitute the primary entrance to the understanding of our ancient Arabic literature. Due totheir awareness of the importance of critical and rhetoric terms,classical scholars attempted to contribute significantly in thisregard. Ibn Abi El-Osboa El-Masseri’ is considered as one of theeminent figures who laid the foundations for critical and rhetoricalterminology through two important books, namely: ‘Tahrir El-Tahbir’and ‘Badia El-Quran’.